An anthropological linguistic study on Maccera’ Bulung ritual - Arafah, Burhanuddin; Kaharuddin, Magfirah Thayyib,; Sahib, Harlina (Opción, 2020)
This research aims at exploring all possible meanings of maccera’ bulung ritual through an anthropological linguistic study. Maccera’ bulung literally means bleeding the chicken for the grown paddy. This research employed a qualitative method with descriptive-naturalistic characteristics. As a result, Maccera’ bulung ritual has three clusters of meaning. The fundamental meaning confirms it as a form of sacrificing and gratitude manifesting for the grown paddy. In conclusion, the ecological meaning reveals that it is ecologically rational. The cultural meaning exposes some ideological and sociological values of society.